Educação como meio, preservação como fim: estudo sobre equipes de conservação de acervos fotográficos - Giselle de Queiroz Rocha (2011)
The objective of this thesis is to discuss the preservation and team building processes through the case study of two conservation projects of documentary photograph collections. I was the Conservation Technical Supervisor in both of the projects. I worked with groups of young people who had no previous experience in the area. The two projects are the Vitae Project of Conservation and Preservation of the Photographic Collection of the Museum of Image and Sound in São Paulo, S.P. (2004-2006) and the Preservation Project of the Photo Collection from the Wanda Svevo Historical Archive, that belongs to the Bienal de São Paulo(2007-2008).The purpose of this research is to consider the ongoing training of assistants, technicians and conservators/restorers who are committed to the job regardless of their level of education, chosen career path, length of contract or position on the team. The argument of this thesis is that in any project, the commitment of the team members should stimulate notonly the interest in learning and replicating technical solutions, but also their participation in the preservation project with critical thinking.